Monomodality versus Combined Therapy in Optic Pathway Gliomas—20-Year Experience from a Singapore Children’s Hospital - Lim, Jia Xu; Tan, Enrica E.K.; Ng, Lee Ping; Seow, Wan Tew; Chang, Kenneth T.E.; Wong, Ru Xin; Looi, Wen Shen; Low, David C.Y.; Low, Sharon Y.Y. (Frontiers in Surgery, 2022)
Introduction The treatment of pediatric optic pathway gliomas (OPG) is challenging. At present, most centers provide individualized treatment to maximize progression free survival (PFS) and minimize morbidity. We aim to report our experience in the management of pediatric OPG, and investigate factors associated with an increased duration of remission after treatment. Methods This is a single-institution study approved by the hospital ethics board. A retrospective review of consecutive OPGs managed from 2000 to 2020 was performed. Patients were divided into those managed with monomodality treatment (MT) and those who received combined therapy (CT). MT included various forms of surgery, chemotherapy and radiotherapy given alone, while CT involves a combination of surgery and adjuvant chemotherapy and/or radiotherapy Results Twenty-two patients were selected for this study. They had 39 treatment cycles; and a total follow up duration of 194.8 patient-years. Most of them were male (63.6%) and presented with visual deficits (72.7%). The mean age at initial presentation was 65 months and majority (86.4%) had their tumors arising directly from the optic chiasm, with 77.3% with hypothalamic extension. One patient had Neurofibromatosis type I (4.5%). The most common histological diagnosis was pilocytic astrocytoma (90.9%), followed by pilomyxoid astrocytoma (9.1%). The 5- and 10- year PFS were 46.2% and 36.4% respectively, while the 5- and 10-year OS were both 100%. When accounting for treatment type, there were 24 treatment cycles with MT (60.0%) and 16 CT (40.0%). After adjustment, treatments with MT were shown to have a shorter mean duration of remission (MT: 45 ± 49, CT: 84 ± 79 months; p = 0.007). Cox regression curve plotted after adjusting for patient’s age at treatment demonstrated a significantly longer PFS in the CT group (p = 0.037). Conclusions Our results suggest a significant survival benefit of CT over MT for affected patients due to the prolonged the duration of disease remission, for both primary and subsequent treatments. Nonetheless, we acknowledge that our study reflects the outcomes of treatment strategies that have evolved over time. We emphasize the need for collective efforts from a dedicated multidisciplinary team and international collaborations for better disease understanding.